Handbook on Geospatial Infrastructure in Support of Census Activities - United Nations Department of Economic; Social Affairs (United Nations, 2013)
The newly revised and renamed Handbook reflects the recommendations of the expert group meetings and regional workshops on geographic information systems (GIS) and census-mapping. It covers both managerial and operational needs in considerable detail. The Handbook addresses organizational and institutional issues that concern statistical agency heads and other managers; and it explicitly addresses technical and practical issues that concern census cartographers and takers. It also contains some examples of country practices in the application of GIS, global positioning systems (GPS) and digital mapping used in censuses contributed by some of these experts.